Penggunaan Model Edukasi Berbasis Aplikasi Mobile Eduma terhadap Perubahan Pengetahuan dan Kepatuhan Ibu Hamil Mengkonsumsi Tablet Tambah Darah - Permatasari, Chyntia Punky; Widyawati, Melyana Nurul; Ramlan, Djamaluddin; Supriyadi, Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the application of an educational model by combining alarms and reminder notifications to consume blood supplement tablets based on a mobile application called EDUMA to change pregnant women's knowledge and compliance with consuming blood supplement tablets. The method used was a quasi-experiment with a one-group pre-test-post-test design. The research results showed that the knowledge difference test obtained a p-value of 0.045 and compliance of 1.000. The conclusions of this research show that the only thing that has a significant difference before and after using the